(untitled) (Journal of Economic Research & Business Administration, 2016)
To date, the “strategy” is one of the key link management. Strategic management – is a modern management tool development organization aimed at enhancing the capacity by achieving competitiveness in the face of increasing changes in the external environment and related uncertainty. Strategy – a guide to be used in the process of achieving the goals and mission of the enterprise. Strategy formation process is always associated with the choice of alternative solutions. Without a developed strategy – a fundamental tool of management – it is impossible to achieve the neces sary unity of strategic actions and decisions in the enterprise.